Identification of Microbiome Associations with Tacrolimus Pharmacokinetics in Adult Hematopoietic Cell Transplantation Using Population Pharmacokinetic and Machine Learning - Moataz E. Mohamed; Shen Cheng; Christopher Staley; Armin Rashidi; Najla El Jurdi; Shernan G. Holtan; Pamala A. Jacobson (Pharmaceutical Research, 2026)
Purpose Tacrolimus (TAC) is known for its high pharmacokinetic variability which cannot be fully explained by pharmacogenomic (PGx) and clinical variables. We identified gut microbiome associated with TAC pharmacokinetic variability in allogeneic hematopoietic cell transplant (HCT) recipients. Methods In this observational study, metagenomic shotgun sequencing was used to analyze stool microbiome collected within ± 10 days from time of first oral TAC trough at steady state. TAC steady state concentrations (222 IV continuous infusion and 436 oral troughs) were modeled to estimate TAC clearance (CL) and oral bioavailability (F) using nonlinear mixed effects modeling. The effect of clinical covariates, PGx variants and concomitant medications on CL and F were evaluated. Machine learning was used to identify bacterial species associated with variability in F and CL. The identified species were incorporated into the final model, and simulations were conducted to estimate their clinical relevance on oral TAC troughs. Results TAC population CL was 6.91 L/h and population F was 64.4%. TAC CL was increased in those with CYP3A5*1 genotype and reduced with voriconazole use and if estimated glomerular filtration rate < 60 ml/min/1.73 m 2 . TAC F increased with laxative use and decreased with corticosteroid use. Limosilactobacillus fermentum had the strongest positive effect on oral TAC troughs while Bacteroides uniformis had the strongest negative effect. Conclusion Gut microbiome contributes to the inter-patient variability in TAC CL and oral F.

Novel Bacteroides bacteriophage-like quantitative real-time PCR assays for human sewage pollution measurement - Jessica R. Willis; Mano Sivaganesan; Brian McMinn; Asja Korajkic; Christopher Staley; Orin C. Shanks (Environmental Pollution, 2025)

Impact of long-term grazing exclusion on soil microbial community composition and nutrient availability - Zhe Wang; Qian Zhang; Christopher Staley; Hailong Gao; Satoshi Ishii; Xiaorong Wei; Jian Liu; Jimin Cheng; Mingde Hao; Michael J. Sadowsky (Biology and Fertility of Soils, 2019)

Influence of Physicochemical Factors on Bacterial Communities Along the Lower Mekong River Assessed by Illumina Next-Generation Sequencing - Christopher Staley; Neelawan Pongsilp; Pongrawee Nimnoi; Thomas Kaiser; Michael J. Sadowsky (Water, Air, & Soil Pollution, 2018)

Fecal pollution: new trends and challenges in microbial source tracking using next‐generation sequencing - Tatsuya Unno; Christopher Staley; Clairessa M. Brown; Dukki Han; Michael J. Sadowsky; Hor‐Gil Hur (Environmental Microbiology, 2018)
Summary In this minireview, we expand upon traditional microbial source tracking (MST) methods by discussing two recently developed, next‐generation‐sequencing (NGS)‐based MST approaches to identify sources of fecal pollution in recreational waters. One method defines operational taxonomic units (OTUs) that are specific to a fecal source, e.g., humans and animals or shared among multiple fecal sources to determine the magnitude and likely source association of fecal pollution. The other method uses SourceTracker, a program using a Bayesian algorithm, to determine which OTUs have contributed to an environmental community based on the composition of microbial communities in multiple fecal sources. Contemporary NGS‐based MST tools offer a promising avenue to rapidly characterize fecal source contributions for water monitoring and remediation efforts at a broader and more efficient scale than previous molecular MST methods. However, both NGS methods require optimized sequence processing methodologies (e.g. quality filtering and clustering algorithms) and are influenced by primer selection for amplicon sequencing. Therefore, care must be taken when extrapolating data or combining datasets. Furthermore, traditional limitations of library‐dependent MST methods, including differential decay of source material in environmental waters and spatiotemporal variation in source communities, remain to be fully understood. Nevertheless, increasing use of these methods, as well as expanding fecal taxon libraries representative of source communities, will help improve the accuracy of these methods and provide promising tools for future MST investigations.

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Detection and differentiation of V ibrio vulnificus and V . sinaloensis in water and oysters of a G ulf of M exico estuary - Christopher Staley; Eva Chase; Valerie J. Harwood (Environmental Microbiology, 2013)
Summary V ibrio vulnificus is a potentially lethal human pathogen that occurs naturally in estuarine waters and shellfish. V ibrio vulnificus was quantified in water and oysters from F lorida's G ulf C oast by plating on mCPC agar, enrichment and plating, and quantitative PCR ( qPCR ). V ibrio vulnificus was detected in 19%, 29%, and 97% of samples respectively by direct plating, qPCR , and enrichment. Only 8% of typical colonies from direct plating were confirmed by PCR for vvhA ; others yielded no or atypically sized amplicons. Sequencing of the 16 S rDNA of 16 vvhA ‐ negative isolates with colony morphology typical of V . vulnificus identified 75% as V . sinaloensis. In vitro growth curves showed that V . sinaloensis grew more rapidly than V . vulnificus in seawater at temperatures ≤ 30°C. In contrast, the growth rate of V . vulnificus in alkaline peptone water was greater than that of V . sinaloensis , suggesting that these species can outcompete one another under conditions that are relevant to environmental parameters or regulatory monitoring regimes respectively. The virulence potential and ecology of V . sinaloensis are poorly understood; however, its phenotypic resemblance to V . vulnificus and the possibility that it could outcompete the pathogen in warm, estuarine waters argue for the need for a better understanding of this newly described V ibrio species.

Analysis of nitrite reductase ( nirK and nirS ) genes and cultivation reveal depauperate community of denitrifying bacteria in the Black Sea suboxic zone - Brian B. Oakley; Christopher A. Francis; Kathryn J. Roberts; Clara A. Fuchsman; S. Srinivasan; James T. Staley (Environmental Microbiology, 2007)
Summary Chemical profiles of the Black Sea suboxic zone show a distribution of nitrogen species which is traditionally associated with denitrification, i.e. a secondary nitrite maximum associated with nitrate depletion and a N 2 gas peak. To better understand the distribution and diversity of the denitrifier community in the Black Sea suboxic zone, we combined a cultivation approach with cloning and sequencing of PCR‐amplified nitrite reductase ( nirS and nirK ) genes. The Black Sea suboxic zone appears to harbour a homogeneous community of denitrifiers. For nirK , over 94% of the sequences fell into only three distinct phylogenetic clusters, and for nirS , a single closely related sequence type accounted for 91% of the sequences retrieved. Both nirS and nirK genes showed a dramatic shift in community composition at the bottom of the suboxic zone, but overall, nirK ‐based community composition showed much greater variation across depths compared with the highly uniform distribution of nirS sequences throughout the suboxic zone. The dominant nirK and nirS sequences differed at the amino acid level by at least 17% and 8%, respectively, from their nearest database matches. Denitrifying isolates recovered from the suboxic zone shared 97% 16S rRNA gene sequence similarity with Marinobacter maritimus . Analysis of the recently discovered nirS gene from the anammox bacterium Candidatus ‘Kuenenia stuttgartiensis’ revealed that mismatches with commonly used primers may have prevented the previous detection of this divergent sequence.